2020
DOI: 10.15439/2020f118
|View full text |Cite
|
Sign up to set email alerts
|

Gradient Boosting Application in Forecasting of Performance Indicators Values for Measuring the Efficiency of Promotions in FMCG Retail

Abstract: In the paper, a problem of forecasting promotion efficiency is raised. The authors propose a new approach, using the gradient boosting method for this task. Six performance indicators are introduced to capture the promotion effect. For each of them, within predefined groups of products, a model was trained. A description of using these models for forecasting and optimising promotion efficiency is provided. Data preparation and hyperparameters tuning processes are also described. The experiments were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
5
0
2
Order By: Relevance
“…Compared to the 'bagging' algorithm that only controls high variance in the model, the 'boosting' algorithm is known to control both bias and variance [45]. Several studies used Gradient Boosting for forecasting demand, as it is more robust to noisy data and uses less memory [46,47].…”
Section: Existing Modelsmentioning
confidence: 99%
“…Compared to the 'bagging' algorithm that only controls high variance in the model, the 'boosting' algorithm is known to control both bias and variance [45]. Several studies used Gradient Boosting for forecasting demand, as it is more robust to noisy data and uses less memory [46,47].…”
Section: Existing Modelsmentioning
confidence: 99%
“…Both the papers talk about applications of marketing intelligence for the fast moving consumer goods. (ii) Application of Modern Machine Learning Methods: Benefits of machine learning methods are described in the work of (lcio, Getúlio, Camilo, Jose, & Douglas, 2019), (Pereira & Frazzon, 2021), (Joanna & Marek, 2020), and (Arvan, Fahimnia., Reisi, & Siemsen, 2018). The paper (lcio, Getúlio, Camilo, Jose, & Douglas, 2019) discusses the use of machine learning techniques in predicting demand for various fast moving consumer goods.…”
Section: Literature Surveymentioning
confidence: 99%
“…The study also indicated that the incorporation of additional explanatory variables can minimize forecasting errors. Similarly, GBM and LightGBM were assessed for their utility in forecasting future sales and promotions, demonstrating decent accuracy [16][17][18]. XGBoost, a widely used model in demand forecasting due to its strong performance in sales forecasting for retail, was found to be a favorable choice [19].…”
Section: Introductionmentioning
confidence: 99%